Association of small, dense low-density lipoprotein cholesterol and galectin-3 in patients with chronic kidney disease. (October 2014) - Savic, Jasna; Zeljkovic, Aleksandra; Bogavac-Stanojevic, Natasa; Simic-Ogrizovic, Sanja; Kravljaca, Milica; Stosovic, Milan; Vekic, Jelena; Spasojevic-Kalimanovska, Vesna; Jelic-Ivanovic, Zorana; Gojkovic, Tamara; Spasic, Slavica
Abstract Background. Dyslipidemia is a common feature of chronic kidney disease (CKD). Although it has been observed that the pattern of lipid abnormalities can vary according to the stage of CKD, there is lack of data concerning the distribution of lipoprotein subclasses at various stages of the disease. In addition, association of proatherogenic small, dense low-density lipoprotein (sdLDL) subclasses with markers of inflammation, such is galectin-3, is not sufficiently explored. The aim of this study was to analyze concentrations and relative proportions of sdLDL-cholesterol (sdLDL-C) and galectin-3 in patients with CKD, with respect to the stage of the disease. Also, we sought possible independent associations of galectin-3 and sdLDL-C. Methods. The study involved 100 hemodialysis (HD) and 50 pre-dialysis patients, together with 94 healthy individuals. SdLDL-C was measured by heparin–magnesium precipitation method. Galectin-3 was measured by ELISA technique. Results. Galectin-3 levels were higher in pre-dialysis and HD patients than in the control group (p < 0.01). The concentration of sdLDL-C was highest in the pre-dialysis group and lowest in HD patients (p < 0.01). CKD patients with increased galectin-3 concentrations had significantly higher relative proportions of cholesterol in sdLDL (% sdLDL-C) than their counterparts with lower galectin-3 levels (p < 0.05). Relative proportion of sdLDL-C was shown to be an independent determinant of galectin-3 concentration. Conclusions. Our results demonstrated alterations in concentrations and proportions of sdLDL-C according to the stages of CKD. The observed independent associations of % sdLDL-C and galectin-3 provide further insight into their complex interaction during the progression of atherosclerosis in CKD.